Cooperatives in Indonesia: Roles, Challenges, and Innovations for the People's Economy - Machasin; Rinaldi, Afdhol; Afifah, Dhiya Dwi (MUI Kota Pekanbaru, 2025)
Cooperatives in Indonesia have long been the main pillar of people's economic development, placing the principles of kinship and mutual cooperation as the foundation. This article aims to analyze the contributions, challenges, and opportunities of cooperatives in supporting people's economic empowerment through a systematic literature review of national and international publications for the period 2013–2025. The results of this study show that cooperatives play a significant role in expanding access to capital, supporting MSMEs, providing alternative financial services, and strengthening community solidarity. Digitalization and technological innovation have been proven to improve governance efficiency, transparency, and member participation, while the development of Sharia cooperatives expands the service base according to Islamic principles. However, several challenges remain, such as weak governance, limited human resources, low financial literacy, and the absence of a special deposit guarantee institution for cooperatives. In the future, strengthening the principles of social solidarity, legal protection reform, and cross-sector collaboration will be key to ensuring that cooperatives are adaptive, inclusive, and remain relevant as the